Genome mining and metabolic profiling of the rhizosphere bacterium Pseudomonas sp. SH-C52 for antimicrobial compounds - van der Voort, Menno; Meijer, Harold; Schmidt, Yvonne; Watrous, Jeramie; Dekkers, Ester; Mendes, Rodrigo; Dorrestein, Pieter C.; Gross, Harald; Raaijmakers, Jos M. (Frontiers in Microbiology, 2015)
The plant microbiome represents an enormous untapped resource for discovering novel genes and bioactive compounds. Previously, we isolated Pseudomonas sp. SH-C52 from the rhizosphere of sugar beet plants grown in a soil suppressive to the fungal pathogen Rhizoctonia solani and showed that its antifungal activity is, in part, attributed to the production of the chlorinated 9-amino-acid lipopeptide thanamycin (Mendes et al. 2011. Science). To get more insight into its biosynthetic repertoire, the genome of Pseudomonas sp. SH-C52 was sequenced and subjected to in silico, mutational and functional analyses. The sequencing revealed a genome size of 6.3 Mb and 5,579 predicted ORFs. Phylogenetic analysis placed strain SH-C52 within the Pseudomonas corrugata clade. In silico analysis for secondary metabolites revealed a total of six nonribosomal peptide synthetase (NRPS) gene clusters, including the two previously described NRPS clusters for thanamycin and the 2-amino acid antibacterial lipopeptide brabantamide. Here we show that thanamycin also has activity against an array of other fungi and that brabantamide A exhibits anti-oomycete activity and affects phospholipases of the late blight pathogen Phytophthora infestans. Most notably, mass spectrometry led to the discovery of a third LP, designated thanapeptin, with a 22-amino-acid peptide moiety. Seven structural variants of thanapeptin were found with varying degrees of activity against P. infestans. Of the remaining four NRPS clusters, one was predicted to encode for yet another and unknown lipopeptide with a predicted peptide moiety of 8-amino acids. Collectively, these results show an enormous metabolic potential for Pseudomonas sp. SH-C52, with at least three structurally diverse lipopeptides, each with a different antimicrobial activity spectrum.